EXPRESSION OF LINGUISTIC POSSIBILITIES IN THE TEXT OF FAIRY TALES - Hamid Bozorov Xo‘Shmurodovich (American Journals Publishing, 2024)
Linguistic networks have become increasingly widespread in World linguistics, and based on this, research work is being carried out that has proven itself. This article reflects on the language possibilities of hisbed fairy tales, the most popular genre of folk oral creativity, reporting from the life of the ancestors of each people, their thoughts, dreams, national-cultural identities, linguistic landscapes.
Keywords: Folk oral creativity, fairy tale, dealecticism, historical lexicon, realism, exoticism, stereotypical text.